THE BENEFIT EFFECT OF GINGER SUPPLEMENTATION AGAINST NICKEL-INDUCED HEPATOTOXICITY IN ALBINO WISTAR RATS - SARA DERBAL; ZINE KECHRID (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was performed to study the potential capacity effect of ginger on the modulation effects of nickel-induced hepatotoxicity. Methods: Thirty-two female albino Wistar rats were divided into four groups of eight each. One served as a control group, the second group (Gi) received ginger 20 g/kg diet, while the third group (Ni) was given nickel 800 mg/L in their drinking water as NiSO46H2O and the fourth group (Ni+Gi) was treated daily with both nickel and ginger. The experiment was lasted for 21 days. Results: The exposure to nickel led to a significant decrease in body weight and food intake with an increase of liver weight. Nickel treatment also produced oxidative liver injury characterized by an increase of glucose, cholesterol, triglyceride, total lipids, bilirubin, malondialdehyde (MDA) concentrations and glutamate-pyruvate transaminase, glutamic oxaloacetic transaminase, and alkaline phosphatase activities. Meanwhile, serum total proteins and liver reduced glutathione (GSH) levels, catalase, GSH peroxidase, and GSH superoxide dismutase activities were decreased. These results are substantiated with marked changes in the histopathology, whereas the supplementation of ginger resulted in a restoration of the previous parameters. Conclusion: It seems that ginger supplementation is a potent factor for reducing the oxidative severity of nickel hepatotoxicity through its antioxidant action.